Технология покрытия металлической основы диоксидом свинца из щелочного электролита - Антонов, А. В. (НТУ "ХПИ", 2013)
Исследован процесс электроосаждения диоксида свинца из щелочного комплексного электролита. Для предотвращения образования донных отложений предложено привести электролит в процессе осаждения в контакт с поверхностью металлического свинца. Для повышения стойкости покрытия предложено ввести в состав электролита добавку силиката натрия в концентрации 0,01…0,02 моль/дм³. Проведены успешные ресурсные испытания анодного покрытия, осажденного без защитного подслоя непосредственно на легированную сталь, в нейтральных и слабощелочных растворах сульфата и хлорида натрия. Полученное покрытие может использоваться в качестве анодного материала в нейтральных и слабощелочных средах.

Process of electrodeposition of dioxide of lead of complex alkaline electrolyte and modified of complex alkaline electrolytes is investigated. For prevention of formation of ground d eposits it is offered to bring electrolyte into contact with a surface of metal lead in the course of sedimentation. For increase of firmness of a covering it is offered to enter into composition of electrolyte an additive of silicate of sodium in concentration 0,01 … 0,02 mol/dm³. It is noticed that particles of silicate of sodium join in a covering mechanically in number of 0,2% and promote formation of more dense and brilliant coverings of tetragonal modification α-PbO₂. Successful resource tests of the anode covering besieged without a protective underlayer directly on stainless steel, in neutral and alkalescent solutions of sulfate and sodium chloride are carried out. The received covering can be used as an anode material in neutral and alkalescent environments.
Keywords: электроосаждение; аноды; электроды биполярные; dioxide of lead; electrodeposition; anode; bipolar electrodes